Accelerating database systems using FPGAs: A survey - Papaphilippou,P; Luk,W (IEEE, 2018)
Database systems are key to a variety of applications, and FPGA-based accelerators have shown promise in supporting high-performance database systems. This survey presents a systematic review of research relating to accelerating analytical database systems using FPGAs. The review includes studies of database acceleration frameworks and accelerator implementations for various database operators. Finally, the survey includes some promising future technologies and discussion on the challenges to be addressed by the future research in this area.